Personality Assessment Inventory for Adolescents: Internal Consistency and Dimensionality in Adolescents from Buenos Aires, Argentina - Stover, Juliana Beatriz; de la Iglesia, Guadalupe; Castro Solano, Alejandro; Fernández Liporace, Mercedes (Pensando Psicología, 2017)
Introduction: The Personality Assessment Inventory for Adolescents (PAI-A) examines the psychopathological symptomatology and variables related to the design of psychotherapeutic interventions. It is composed of 264 items for use in the clinical assessment of adolescents between 12-18 years old. Validity, clinical, treatment-related, and interpersonal relationship scales are included. Purpose: This paper presents psychometric analyses of the Personality Assessment Inventory for Adolescents. Method: The participants were 1,002 adolescents (50.3% women, 49.7% men, Mage=14.99, SD=1.88) living in Buenos Aires (Argentina) and on the outskirts. Cronbach’s alphas were calculated to estimate internal consistency, with excellent values for clinical, treatment-related and interpersonal relationship scales, and acceptable values for validity scales and subscales. Results: Dimensionality was examined by principal component analysis with a varimax rotation. A four-factor structure was isolated by including the 22 scales, whereas two factors were obtained when analyzing the 11 clinical scales. Conclusions: We provide evidence of the psychometric quality of the pai-a for use with adolescents from Buenos Aires, filling a gap in local psychological assessment. Further research should extend these psychometric quality analyses, and replicate the procedures in clinical samples.